2021
DOI: 10.1002/jia2.25785
|View full text |Cite
|
Sign up to set email alerts
|

“It's a burden, it's a nuisance. I wish I didn't have these other ailments”: a qualitative exploration of comorbidities management among older people living with HIV who use drugs in Vancouver, British Columbia

Abstract: Introduction People living with HIV (PLHIV) who use illicit drugs (other than or in addition to cannabis) are living longer due to antiretroviral therapy (ART). Older PLHIV who use drugs have an increased risk for comorbidities, and managing multiple health conditions is a growing concern among this population. However, in‐depth understandings of the lived realities and complexities of living with HIV alongside comorbidities among older PLHIV who use drugs remain limited. We sought to explore how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Being diagnosed with HIV or being vulnerable to HIV in the pre-ART era may have caused a significant burden in the past 5 , 16 , 35 39 . The predominant and negative influence of HIV shared by participants in our study was described to have improved due to ART, PrEP, and U = U, but it did not disappear 5 , 33 , 40 42 . Improvements in clinical management in the ART era meant new discomforts for participants, such as the side effects of ART.…”
Section: Discussioncontrasting
confidence: 49%
“…Being diagnosed with HIV or being vulnerable to HIV in the pre-ART era may have caused a significant burden in the past 5 , 16 , 35 39 . The predominant and negative influence of HIV shared by participants in our study was described to have improved due to ART, PrEP, and U = U, but it did not disappear 5 , 33 , 40 42 . Improvements in clinical management in the ART era meant new discomforts for participants, such as the side effects of ART.…”
Section: Discussioncontrasting
confidence: 49%
“…Polypharmacy was significantly associated with meeting deprescribing criteria ( p = 0.008) Limitations to this study include the use of dispensing records as some information may be missing and the reliability of the information depends on the inputting physician. Furthermore, the small sample size limits the generalisability of the data Rozanova et al, 2020 (Ukraine) [ 97 ] n = 123 Age = 55–81 years Community Data were collected via telephone surveys Older PLWH with substance misuse disorders maintained their HIV and substance use disorder therapies over the Covid-19 lockdown, however, social support was highlighted to be critical to avoid treatment interruptions A limitation to this study is that telephone surveys may have led to social desirability bias in participant answers Chayama et al, 2021 (Canada) [ 55 ] n = 42 Age = 50+ years Community Semi-structured in-depth interviews were used to collect data Participants viewed co-morbidities as more urgent and prioritised them over HIV. Access to care for co-morbidities were hindered by stigma and discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…Older PLWH are more likely to be affected by anxiety, depression, cancer, chronic kidney disease (CKD), chronic pain, diabetes, hypertension, osteoporosis, hepatitis B/C infections than HIV-negative individuals [ 31 , 32 , 34 , 36 , 39 , 42 – 45 , 47 , 51 , 55 , 58 , 61 ]. A study comparing HIV-positive older males to their HIV-negative counterparts found that older participants were six times more likely to be diagnosed with osteoporosis [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations